Teknologi Tepat Guna Dan Digitalisasi Marketing Untuk Meningkatkan Penjualan - Munfaqiroh, Siti; Aryani, Dwi Nita; Nursasi, Enggar (Jurnal ABM Mengabdi, 2025)
This community service program aims to increase the production and sales capacity of MSME partners through the application of appropriate technology and optimization of digital marketing. The target partner is “Sambal Mama Ni” in Malang City, which faces limitations in production capacity and has not yet optimized its digital marketing strategy or financial reporting. The solutions provided include the provision of a 30 liter spice grinder to support increased production, the development and training of website management as a means of promotion and sales, and assistance in preparing accurate and systematic financial reports. The results of the activity showed an increase in production efficiency, expanded marketing reach through an integrated website, and improved partner understanding of financial record-keeping. With this guidance and training, the partner gained new insights and knowledge that can be applied, thereby hopefully driving sustainable business growth and empowering the community economically.